Ecological effects of foreshore stabilisation on temperate estuarine fish assemblages - Hayden Swift; Megan Huggett; Michael Stat; David Wainwright; Troy Gaston (Ecological Engineering, 2026)

The Pb, Sr and Nd isotopic composition of the upper continental crust: An Australian perspective - Candan U. Desem; Jon Woodhead; Patrice de Caritat; Roland Maas; David C. Champion; Anthony Dosseto; Ashlea Wainwright; Graham Carr (Chemical Geology, 2025)

Determining the species composition of the shark fin trade in Singapore: a globally significant Southeast Asian market - Nathalia Murillo Rengifo; Christina Pei Pei Choy; Jasmine Anya Putri Gowidjaja; Mariana Quesada Urera; Caroline Kibat; David J. Nott; Benjamin J. Wainwright (Reviews in Fish Biology and Fisheries, 2024)

Sit and survive: predation avoidance by cryptobenthic coral reef fishes - Michalis Mihalitsis; David R. Bellwood; Peter C. Wainwright (Marine Biology, 2024)

Investigating the Sensitivity of Marine Fog to Physical and Microphysical Processes Using Large-Eddy Simulation - Charlotte Wainwright; David Richter (Boundary-Layer Meteorology, 2021)

A Lagrangian Cloud Model for the Study of Marine Fog - David H. Richter; Theodore MacMillan; Charlotte Wainwright (Boundary-Layer Meteorology, 2021)

Measurements of the Temperature Structure-Function Parameters with a Small Unmanned Aerial System Compared with a Sodar - Timothy A. Bonin; David C. Goines; Aaron K. Scott; Charlotte E. Wainwright; Jeremy A. Gibbs; Phillip B. Chilson (Boundary-Layer Meteorology, 2015)

Marine environment‐based forecasting of coho salmon ( Oncorhynchus kisutch ) adult recruitment - DAVID E. RUPP; THOMAS C. WAINWRIGHT; PETER W. LAWSON; WILLIAM T. PETERSON (Fisheries Oceanography, 2012)
Generalized additive models (GAMs) were used to investigate the relationships between annual recruitment of natural coho salmon ( Oncorhynchus kisutch ) from Oregon coastal rivers and indices of the physical ocean environment. Nine indices were examined, ranging from large‐scale ocean indicators, e.g., Pacific Decadal Oscillation (PDO), to indicators of the local ecosystem (e.g., coastal water temperature near Charleston, OR). Generalized additive models with two and three predictor variables were evaluated using a set of performance metrics aimed at quantifying model skill in short‐term (approximately 1 yr) forecasting. High explanatory power and promising forecast skill resulted when the spring/summer PDO averaged over the 4 yr prior to the return year was used to explain a low‐frequency (multi‐year) pattern in recruitment and one or two additional variables accounted for year‐to‐year deviations from the low‐frequency pattern. More variance was explained when averaging the predictions from a set of models (i.e., taking the ensemble mean) than by any single model. Making multiple forecasts from a set of models also provided a range of possible outcomes that reflected, to some degree, the uncertainty in our understanding of how salmon productivity is driven by physical ocean conditions.

High-density single nucleotide polymorphism array analysis in patients with germline deletions of 22q11.2 and malignant rhabdoid tumor - Eric M. Jackson; Tamim H. Shaikh; Sridharan Gururangan; Marilyn C. Jones; David Malkin; Sarah M. Nikkel; Craig W. Zuppan; Luanne M. Wainwright; Fan Zhang; Jaclyn A. Biegel (Human Genetics, 2007)

Ecomorphology of Locomotion in Labrid Fishes - Peter C. Wainwright; David R. Bellwood; Mark W. Westneat (Environmental Biology of Fishes, 2002)

Mapping the multiple self-healing squamous epithelioma (MSSE) gene and investigation of xeroderma pigmentosum group A (XPA) and PATCHED (PTCH) as candidate genes - F. M. Richards; David R. Goudie; Wendy N. Cooper; Quitz Jene; Inês Barroso; Carol Wicking; Brandon J. Wainwright; M. A. Ferguson-Smith (Human Genetics, 1997)